Immigration nation : aid, control, and border politics in Morocco - Gazzotti, Lorena, 1991- (Cambridge University Press, 2021)
Over the past forty years, countries in the Global North have increasingly restricted their migration policies to reduce the arrival of migrants. As part of this, development aid has become a central tool in the migration control strategy pursued by European countries and the US, with donors, International Organisations and NGOs becoming prominent actors. In this book, Lorena Gazzotti shows that migration control is not only exercised through fences and deportation. Building on extensive research in Morocco, Gazzotti shows that aid marks the rise of a substantially different mode of migration containment, one where power works beyond fast violence, and its disciplinary potential is augmented precisely by its elusiveness. Where existing studies on border externalisation have essentialised donors, International Organisations and NGOs, with countries of 'origin' and 'transit' as compliant subcontractors, and border control as a neat form of intervention, this nuanced study unsettles such assumptions, to show that bordering happens in everyday, mundane fashions, far away from the spectacle of border violence.